The Relationship between Gadget Addiction and Sleep Quality among Adolescents at SMK Negeri in Purbalingga - Hidayat, Arif Imam; Mustikasari, Sherina; Nani, Desiyani (Journal of Bionursing, 2024)
Background: The global prevalence of sleep quality disorders ranges from 15,3% to 39,2%. According to Indonesian data, as much as 63% of adolescents' sleep quality needs have not been met. Poor sleep quality will result from excessive device use throughout the day. Sleep deprivation can affect sleep patterns and interfere with social interactions. Methods: This quantitative study uses a correlation approach and data collection techniques for gadget addiction scales, namely the Smartphone Addiction Scale (SAS) and Sleep Quality Scale (SQS). The subjects of this study were 48 students of Central Java State Vocational Schools in Purbalingga. The sampling technique of this study used total sampling for data analysis techniques using non-parametric analysis techniques, namely Spearman rho analysis. Results: A correlation value of p = 0.00 < 0.05 means that H0 is not accepted. The correlation coefficient between the two variables is equal to 0.744. So it can be interpreted that there is a strong relationship between gadget addiction and sleep quality among adolescents. Conclusion: There is a significant relationship between gadget addiction and sleep quality in adolescents.